Jasmin Vardimon Dance Company - Felsenburg, Ben (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of Jasmin Vardimon Dance Company. PALABRAS CLAVE: Jasmin Vardimon Dance Company, Lullaby.
Dentro del apartado "Dance Now".